Product type and the risk of inhibitor development in nonsevere haemophilia A patients: a case‒control study. (22nd March 2020) - van Velzen, Alice S.; Eckhardt, Corien L.; Peters, Marjolein; Oldenburg, Johannes; Cnossen, Marjon; Liesner, Ri; Morfini, Massimo; Castaman, Giancarlo; McRae, Simon; van der Bom, Johanna G.; Fijnvandraat, Karin; ,
Summary: Inhibitor development is a major complication of treatment with factor VIII concentrates in nonsevere haemophilia A. It has been suggested that plasma‐derived factor VIII (FVIII) concentrates elicit fewer inhibitors than recombinant FVIII concentrates, but studies in severe haemophilia A patients have shown conflicting results. We designed a case‒control study to investigate the clinical and genetic risk factors for inhibitor development in nonsevere haemophilia A patients. We investigated whether the type of FVIII concentrate was associated with inhibitor development in nonsevere haemophilia A patients. This nested case‒control study includes 75 inhibitor patients and 223 controls, from a source population of the INSIGHT study, including all nonsevere haemophilia A patients (FVIII:C 2–40%) that were treated with FVIII concentrates in 33 European and one Australian centre. Cases and controls were matched for date of birth and cumulative number of exposure days (CED) to FVIII concentrate. A conditional logistic regression model was used to calculate unadjusted and adjusted odds ratios. No increased risk for inhibitor development was found for any type of FVIII concentrate; either when comparing recombinant FVIII concentrates to plasma‐derived FVIII concentrates (adjusted odds ratio 0·96, 95% confidence interval (CI) 0·36–2·52) or for specific types of FVIII concentrates.